Serum amyloid A4 is a procoagulant apolipoprotein that it is elevated in venous thrombosis patients. Issue 2 (29th December 2019) - Fernández, José A.; Deguchi, Hiroshi; Elias, Darlene J.; Griffin, John H.
Abstract: Background: Serum amyloid A4 (SAA4) is an apolipoprotein that is in the SAA family and it is constitutively translated. Previously, acute‐phase SAA1 and SAA2 levels were associated with venous thromboembolism (VTE). Objective: We investigated the association of plasma SAA4 with VTE and the role of SAA4 in coagulation. Patients and Methods: The association of SAA4 with VTE in a case‐control study of adult VTE subjects (N = 113 each group) and the effects of recombinant SAA4 on plasma blood coagulation assays and prothrombin activation initiated by factor Xa were evaluated. Results: Plasma SAA4 levels in VTE subjects were higher vs. controls (48.1 vs. 38.4 µg/mL; P < .001). Elevated plasma SAA4 level (above the 90th percentile of controls) was associated with increased VTE occurrence (odds ratio, 3.8; 95% confidence interval, 1.8‐8.0). This association remained significant after the adjustment for acute‐phase SAA level, suggesting that SAA4 associated with VTE is independent of acute‐phase SAA. Two isoforms of SAA4, that is, glycosylated and nonglycosylated SAA4 isoforms, were each higher in VTE patients. When recombinant SAA4 was added to plasma, it shortened factor Xa‐1‐stage clotting times, showing that it enhances clotting in plasma. In reaction mixtures containing purified factors Xa and Va and prothrombin, recombinant SAA4 increased prothrombin activation, showing that it enhances prothrombinase activity. Conclusion: Elevated plasma constitutive SAA4 levels were linked to VTE in adults, and SAA4 can enhance thrombin generation in plasma. Our data highlight a previously unknown procoagulant activity of SAA4 that appears to be related to risk of venous thrombotic events.